Epilepsy in Mowat–Wilson syndrome: Delineation of the electroclinical phenotype123. Issue 2 (15th January 2013) - Cordelli, Duccio Maria; Garavelli, Livia; Savasta, Salvatore; Guerra, Azzurra; Pellicciari, Alessandro; Giordano, Lucio; Bonetti, Silvia; Cecconi, Ilaria; Wischmeijer, Anita; Seri, Marco; Rosato, Simonetta; Gelmini, Chiara; et al.
Abstract Mowat–Wilson syndrome (MWS) is a genetic disease caused by heterozygous mutations or deletions of the ZEB2 gene and is characterized by distinctive facial features, epilepsy, moderate to severe intellectual disability, corpus callosum abnormalities and other congenital malformations. Epilepsy is considered a main manifestation of the syndrome, with a prevalence of about 70–75%. In order to delineate the electroclinical phenotype of epilepsy in MWS, we investigated epilepsy onset and evolution, including seizure types, EEG features, and response to anti‐epileptic therapies in 22 patients with genetically confirmed MWS. Onset of seizures occurred at a median age of 14.5 months (range: 1–108 months). The main seizure types were focal and atypical absence seizures. In all patients the first seizure was a focal seizure, often precipitated by fever. The semiology was variable, including hypomotor, versive, or focal clonic manifestations; frequency ranged from daily to sporadic. Focal seizures were more frequent during drowsiness and sleep. In 13 patients, atypical absence seizures appeared later in the course of the disease, usually after the age of 4 years. Epilepsy was usually quite difficult to treat: seizure freedom was achieved in nine out of the 20 treated patients. At epilepsy onset, the EEGs were normal or showed only mild slowing of background activity. During follow‐up, irregular, diffuse frontally dominant and occasionally asymmetric spike and waves discharges were seen in most patients. Sleep markedly activated these abnormalities, resulting in continuous or near‐to‐continuous spike and wave activity during slow wave sleep. Slowing of background activity and poverty of physiological sleep features were seen in most patients. Our data suggest that a distinct electroclinical phenotype, characterized by focal and atypical absence seizures, often preceded by febrile seizures, and age‐dependent EEG changes, can be recognized in most patients with MWS. © 2013 Wiley Periodicals, Inc.